Menganalisis Koperasi Simpan Pinjam dan Klaster Unggulan Terhadap Industrialisasi - Putra M, Johanes; Yasin, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research investigates the roles of savings and loan cooperatives (SLCs) and industrial clusters in supporting industrialization. SLCs, as member-based financial entities, provide crucial funding access for small and medium enterprises (SMEs) and promote local economic empowerment through inclusive financial services. On the other hand, industrial clusters, characterized by a geographic concentration of related businesses and institutions, drive efficiency, innovation, and market development within the industrial sector.The study aims to analyze the interaction between SLCs and industrial clusters and their impacts on industrialization. Findings indicate that synergy between these entities can create an ecosystem that supports sustainable and inclusive industrial growth, enhances regional competitiveness, and improves the economic welfare of local communities.In conclusion, the synergistic cooperation between SLCs and industrial clusters holds significant potential to accelerate the industrialization process. Therefore, this research recommends support from governments, financial institutions, and other stakeholders to facilitate such collaboration for advancing the industrial sector and promoting sustainable economic development.